Formulation of pH and temperature dual-responsive Pickering emulsion stabilized by chitosan-based microgel for recyclable biocatalysis. (1st August 2020) - Wang, Yuxian; Zhu, Liying; Zhang, Hongman; Huang, He; Jiang, Ling
Highlights: CS-g-PNIPAM microgel have been accomplished via one-pot green synthesis. The smart microgel showed pH and temperature dual-responsive properties. The Pickering emulsion stabilized by microgel showed same dual-response. CS-g-PNIPAM stabilized emulsion showed promising recyclable biocatalysis. Abstract: Developing green and smart emulsifier for multiple responsive Pickering emulsion has been a great significance to many industries. Therefore, a novel emulsifier, poly (N-isopropylacrylamide) (PNIPAM) grafted chitosan (CS) microgel (CS-g-PNIPAM), was obtained, which exhibited swelling and deswelling behaviors in response to abrupt changes of pH and temperature. The resulting O/W Pickering emulsion was also sensitive to pH and temperature, and adjusting either the pH from 5.0 to 9.0 or temperature from 25 to 45 ℃ could effectively trigger oil-water separation and emulsification on demand. Based on it, a biphasic biocatalysis was applied to evaluate the catalytic capacity of this approach. The hydrolysis of fish oil and esterification of oleic acid with n -octanol were performed successfully. Meanwhile, the easy separation of products and good recyclability could be realized by reversibly increasing or decreasing temperature. The green system provides a great potential for the application of biopolymers in biphasic interfacial biocatalysis.